Structure and Chemical Analysis of Major Specialized Metabolites Produced by the Lichen Evernia prunastri. Issue 1 (10th January 2020) - Staples, Richard; LaDuca, Robert L.; Roze, Ludmila V.; Laivenieks, Maris; Linz, John E.; Beaudry, Randolph; Fryday, Alan; Schilmiller, Anthony L.; Koptina, Anna V.; Smith, Benjamin; Trail, Frances
Abstract: We performed comparative profiling of four specialized metabolites in the lichen Evernia prunastri, collected at three different geographic locations, California and Maine, USA, and Yoshkar Ola, Mari El, Russia. Among the compounds produced at high concentrations that were identified in all three specimens, evernic acid, usnic acid, lecanoric acid and chloroatranorin, evernic acid was the most abundant. Two depsidones, salazinic acid and physodic acid, were detected in the Yoshkar‐Ola collection only. The crystalline structure of evernic acid (2‐hydroxy‐4‐[(2‐hydroxy‐4‐methoxy‐6‐methylbenzoyl)oxy]‐6‐methylbenzoate) (hmb) revealed two crystallographically and conformationally distinct hmb anions, along with two monovalent sodium atoms. One hmb moiety contained an exotetradentate binding mode to sodium, whereas the other exhibited an exohexadentate binding mode to sodium. Embedded edge‐sharing Na2 O8 n sodium‐oxygen chains connected the hmb anions into the full three‐dimensional crystal structure of the title compound. The crystal used for single‐crystal X‐ray diffraction exhibited non‐merohedral twinning. The data suggest the importance of the acetyl‐polymalonyl pathway products to processes of maintaining integrity of the lichen holobiont community. Abstract :